Debates in modern languages education - Driscoll, Patricia, 1953-; Macaro, Ernesto; Swarbrick, Ann (London : Routledge, 2014)
'Debates in Foreign Languages Education offers a comprehensive introduction and synthesis of the major themes and research evidence in language learning and teaching today, providing an up-to-date, authoritative review of traditional and contemporary issues in language teaching. With chapters by leading experts in the field, thematic sections explore and consider:the importance of a wide range of different knowledge bases and skills for effective teachinghow to become expert practitionersapproaches to teaching with reference to relevant theories, complex constructs, and empirical researchthe innovations and ideas that shape and will shape the discipline for the next decade. Each thought-provoking chapter is supported by reference to further reading and additional material to encourage deeper exploration which will help the reader to fully engage in the debates presented. This book is a valuable resource for any student or practising teacher engaged in initial teacher education, continuing professional development and Masters level study'--
Includes bibliographical references : (pages 273-309) and index.
Keywords: Language and languages -- Study and teaching; Second language acquisition -- Study and teaching; Languages, Modern -- Study and teaching; Language teachers -- Training of